Pengaruh Pemberian Temulawak terhadap Penurunan Dismenorea pada Remaja Desa Batuwarno - Dhea Ayu Retno Palupi; Enny Yuliaswati (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Background: Dysmenorrhea is a common menstrual pain experienced by adolescent girls, often interfering with daily activities. Curcuma xanthorrhiza contains curcuminoids with anti-inflammatory and analgesic properties, making it a potential non-pharmacological treatment for menstrual pain. A preliminary study in Batuwarno Village showed a high prevalence of dysmenorrhea among adolescents. Objective: To determine the effect of Curcuma xanthorrhiza consumption on the reduction of dysmenorrhea in adolescents in Batuwarno Village. Methods: This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 24 adolescent girls with dysmenorrhea, selected using consecutive sampling. The intervention involved administering 200 ml of boiled Curcuma xanthorrhiza twice a day for one day. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon test. Results: The average pain score before the intervention was 6.54, and after the intervention, it decreased to 1.50. The Wilcoxon test yielded a Z value of -4.448ᵇ, where the negative Z value indicates that the more the intervention is given, the more the experienced pain decreases. The resulting p-value was 0.000 (p < 0.05), indicating a significant effect of Curcuma xanthorrhiza administration on the reduction of dysmenorrhea. Conclusion: Curcuma xanthorrhiza is effective in reducing dysmenorrhea in adolescents and can be considered a non-pharmacological alternative for managing menstrual pain.